Perceptions of, and reactions to, environmental heat: a brief note on issues of concern in relation to occupational health - Delia Rizpah Hollowell (Taylor & Francis Group, 2010)
Average temperatures around the world are already increasing, and climate change projections suggest that global mean temperatures will continue to rise. As the effects, and projected effects, of climate change are becoming clearer, it is more apparent that the health effects of heat exposure will need further investigation. The risks associated with heat exposure are especially relevant to understandings of occupational health for people involved in labouring or agricultural work in low-income countries. This review is a partial look at the ways in which issues surrounding heat exposure and occupational health have been treated in some of the available literature. This literature focuses on military-related medical understandings of heat exposure as well as heat exposure in working environments. The ways that these issues have been treated throughout the literature reflect the ways in which technologies of observation are intertwined with social attitudes. The effects of heat on the health of working people, as well as identification of risk groups, will require further research in order to promote prophylactic measures as well as to add to understandings of the actual and potential consequences of climatic change.